Bloodguard [large type] - Robson, Cecy (Thorndike Press Large Print, 2025)
"Everything in the Kingdom of Arrow is a lie. Leith of Grey thought coming to this new land and volunteering to fight in the gladiator arena would earn him enough gold to save his dying sister. He thought there was nothing left to lose. He was wrong - and they took everything. His hope. His freedom. His very humanity. Then Leith meets Maeve, an elven royal who is everything he despises. Everything he should hate. Until the alluring princess offers him the one thing he needs most: a chance to win the coveted title of Bloodguard - and his freedom. But in a kingdom built on secrets and lies, hope doesn't come cheap. Nor will his ultimate revenge." --